5(y-1)+16(2y+3)=3(2y-7)

Simple and best practice solution for 5(y-1)+16(2y+3)=3(2y-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y-1)+16(2y+3)=3(2y-7) equation:



5(y-1)+16(2y+3)=3(2y-7)
We move all terms to the left:
5(y-1)+16(2y+3)-(3(2y-7))=0
We multiply parentheses
5y+32y-(3(2y-7))-5+48=0
We calculate terms in parentheses: -(3(2y-7)), so:
3(2y-7)
We multiply parentheses
6y-21
Back to the equation:
-(6y-21)
We add all the numbers together, and all the variables
37y-(6y-21)+43=0
We get rid of parentheses
37y-6y+21+43=0
We add all the numbers together, and all the variables
31y+64=0
We move all terms containing y to the left, all other terms to the right
31y=-64
y=-64/31
y=-2+2/31

See similar equations:

| 10*62=n*6.2 | | y=-9-4-9 | | 0*53=n*34 | | 3(4x+1)=6x+2 | | n/5.9=11 | | 2x+8-x=3x-12 | | 9.8x=63.7 | | -5x=10-15. | | 28*n=7*12 | | 5x=10-15. | | (-6d=2)-(7=2d) | | 36*n=36 | | p/1.2=25/15 | | 17/15+s/15=-4 | | 18+30=6(2x-1) | | 13+4K=13+5k | | -67b+6=9b+43 | | 1=8x-6=2=7x | | 8p-8=6(-7p+7) | | 5x-81=360 | | 63-x=2x=3 | | (7x^2-27)=(6x^2-6x) | | 4(m-4)-6=-31-5m | | 9^2-18=8^2-7x | | 18-2|c+7|=12 | | -42v+33=8v | | (9x-18)=(8x-7x) | | 1/m+2-4=4/m+2 | | 4x+92=0+80x | | -4x+3(x-8)=7(2x-4)-11 | | (|m|)/4=5 | | -4x+3(x-8)=7 |

Equations solver categories